Characterization of Th17 and FoxP3+ Treg Cells in Paediatric Psoriasis Patients. (March 2016) - Zhang, L.; Li, Y.; Yang, X.; Wei, J.; Zhou, S.; Zhao, Z.; Cheng, J.; Duan, H.; Jia, T.; Lei, Q.; Huang, J.; Feng, C.
Abstract: Psoriasis is one of the most common inflammatory skin conditions affecting both children and adults. Growing evidence indicates that T‐helper 17 (Th17) cells and CD4 + CD25 + regulatory T (Treg) cells play an important role in the pathogenesis of psoriasis. However, the relationship between Th17 and Treg cells and their dynamic variations in paediatric psoriasis remain unclear. In this study, we found that both Th17 and FoxP3 + Treg cells and the ratio of Th17 to Treg cell frequency in the peripheral circulation were increased in patients with paediatric psoriasis and were positively correlated with the disease severity. The function of Treg to suppress CD4 + CD25 − T cell proliferation and IFN‐γ secretion was impaired during the onset of psoriasis. After disease remission, both the Th17 and Treg cell frequencies were decreased, and the suppressive function of the Treg cells was obviously restored. However, neither Treg cells from the disease onset nor those after remission can regulate IL‐17 secretion by CD4 + T cells. These findings will further our understanding of the associations between Th17 and Treg cells in paediatric psoriasis and their influence on disease severity.